Evaluation of virtual desktop infrastructure using user workload simulator / Muhammad Fadhli Mohd Nadzri - Mohd Nadzri, Muhammad Fadhli (2015)
Numerous of Virtual Desktop Infrastructure (VDI) solution available in market has invokes a reason to evaluate and compare those VDI solutions. One of important component for VDI is VDI host. Therefore, it is important to use an efficient VDI host. In this thesis, a VDI host evaluation is done by using three metric that is Virtual Machine (VM) density, IOPS (Input/output Operation per Second) consumption, and network bandwidth utilization. Two tools have been developed in order to evaluate the VDI host that is User Workload Simulator and VDI Host Evaluator. User Workload Simulator use to do user workload test, while VDI Host Evaluator will processed and evaluate the collected data from the test to indicate which VDI host is better between two VDI host. User workload categorized into four profiles which is light, medium, heavy and multimedia user profiles. User Workload Simulator will run the test based on those profiles. While user workload test is running, utilization data of VM resource will be collected by Performance Monitor. The test done on two VDI host, that are VDI A host and VDI B host. The collected data from both VDI host will produce estimated VM density, IOPS consumption and network bandwidth utilization per host. By using VDI Host Evaluator, the three VDI host metric mention previously will be compared and evaluated. VDI Host Evaluator will indicate which VDI host is better after done evaluating those three metrics.